-2(2x-1)+1=-4x+3

Simple and best practice solution for -2(2x-1)+1=-4x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(2x-1)+1=-4x+3 equation:


Simplifying
-2(2x + -1) + 1 = -4x + 3

Reorder the terms:
-2(-1 + 2x) + 1 = -4x + 3
(-1 * -2 + 2x * -2) + 1 = -4x + 3
(2 + -4x) + 1 = -4x + 3

Reorder the terms:
2 + 1 + -4x = -4x + 3

Combine like terms: 2 + 1 = 3
3 + -4x = -4x + 3

Reorder the terms:
3 + -4x = 3 + -4x

Add '-3' to each side of the equation.
3 + -3 + -4x = 3 + -3 + -4x

Combine like terms: 3 + -3 = 0
0 + -4x = 3 + -3 + -4x
-4x = 3 + -3 + -4x

Combine like terms: 3 + -3 = 0
-4x = 0 + -4x
-4x = -4x

Add '4x' to each side of the equation.
-4x + 4x = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = -4x + 4x

Combine like terms: -4x + 4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 5x^2+7xy-6y^2=0 | | 3x=(2x-2)(m+5) | | y=x^2+14x | | 2y=0-14 | | 0=3v-5v | | 2x^2-17xy+30y^2=0 | | 9x-3=9(x-1) | | 8(2x+4)-7(2x+3)=51 | | 6.4/m=2 | | 59/6 | | 4(5x-(3-5y+4x)+4y)= | | X-6.6=4.1 | | 5d-6=-21 | | 65x+2=90 | | (x^2+10x-5)=0 | | 3(f-12)=-12 | | 18c^2=6c+0 | | 0.09x+5=22 | | 18c^2z=6c+0 | | 2*c=6.4 | | -3(x+5)=18 | | (a^-3/3b)^4 | | 6(-2x+1)=-54 | | X+6.6=4.1 | | 3(f-2)=-12 | | x^3/4y^-1/4/x^1/2y^-1/2 | | 16/3/x^1/3 | | x/3=2.6 | | 5/9(f-32)=62.1 | | 0.09x+5=29 | | 38.4=6v | | 18.75*m=3 |

Equations solver categories